Investigations into effective fly ash used in concrete - Rudžionis, Žymantas; Ivanauskas, Ernestas (Journal of Civil Engineering and Management, 2004)
This work presents a study on the influence of thermal‐electrical fly ash on the cement paste hydration processes, investigation into cement stone, mortar, ordinary and self‐compacting concrete, when cement was replaced by fly ash (5–33%). It was estimated that cement stone and cement paste prepared from fly ash and cement properties were better when polycarboxylic superplasticiser “Visco Crete‐3” was used. It was established that admixture of fly ash influences the processes of cement hydration: the amount of free Ca(OH)2 in cement stone was decreased and amount of stable calcium hydro silicates was increased. It allows to state, that cement stone becomes more corrosion‐resistant and more durable. When fly ash admixture is applied in ordinary concrete production, it is possibility to reduce cement expenditures up to 33% and in self‐compacting concrete production, segregation and separation of water decreases. Data of investigations on hardened concrete showed that fly ash increases compressive strength (up to 15%), decreases shrinkage strains (up to 31,6%), increases plastic deformations (up to 38%), modulus of elasticity (up to 15 %) and modifies other concrete properties. First Published Online: 14 Oct 2010